Poor nutrition and chronic diseases among minority populations - Megan Ralfe (Shahid Beheshti University of Medical Sciences, 2021)
Minority populations are more subject to chronic diseases such as obesity, hypertension, and various cancers due to their lack of access to quality food and knowledge of adequate nutrition. Theories such as the Health Belief Model and the Social Cognitive Theory have been used throughout various studies to understand why minority populations are more likely to develop chronic diseases stemmed from poor nutrition. Components such as socioeconomic status, education, median household income, ethnicity, interpersonal and intrapersonal factors were all analyzed using the aforementioned theories to understand why minorities are disproportionately affected in regard to receiving adequate nutrition and prevention of chronic diseases. Various government policies and programs have been created to aid minority families in purchasing quality food and to promote more measures against chronic diseases. Further research in understanding why minority populations are disproportionately affected may include systemic and environmental racism, including administration of preventive healthcare resources.